2022
DOI: 10.1038/s41522-022-00348-2
|View full text |Cite
|
Sign up to set email alerts
|

One-year supplementation with Lactobacillus reuteri ATCC PTA 6475 counteracts a degradation of gut microbiota in older women with low bone mineral density

Abstract: Recent studies have shown that probiotic supplementation has beneficial effects on bone metabolism. In a randomized controlled trial (RCT) we demonstrated that supplementation of Lactobacillus reuteri ATCC PTA 6475 reduced bone loss in older women with low bone mineral density. To investigate the mechanisms underlying the effect of L. reuteri ATCC PTA 6475 on bone metabolism, 20 women with the highest changes (good responders) and the lowest changes (poor responders) in tibia total volumetric BMD after one-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Next, we removed 421 studies due to the following reasons: lack of required data as indicated in the inclusion/exclusion criteria, not having an appropriate control group, and co‐supplementation of probiotics and/or synbiotics with other active ingredients. However, there were some studies that were removed due to having the same sample of participants 60–83 and hence were treated as a single study. Finally, 200 unique RCTs with 220 effect sizes were included for quantitative and qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we removed 421 studies due to the following reasons: lack of required data as indicated in the inclusion/exclusion criteria, not having an appropriate control group, and co‐supplementation of probiotics and/or synbiotics with other active ingredients. However, there were some studies that were removed due to having the same sample of participants 60–83 and hence were treated as a single study. Finally, 200 unique RCTs with 220 effect sizes were included for quantitative and qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In most related studies, supplementation with probiotics increased BMD values ( Yu et al, 2021 ). For example, supplementation with Lactobacillus reuteri ATCC PTA 6475 reduced bone loss in older women with low BMD ( Li et al, 2022 ). Lactobacillus acidophilus inhibited bone loss and increased bone heterogeneity by modulating Treg-Th17 cell function in osteoporotic mice ( Dar et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A decade of research focused on understanding gut-osteoporosis crosstalk has yielded some success alleviating osteoporosis by manipulating the gut. For example, Lactobacillus reuteri ATCC PTA 675 supplementation was found to enrich short chain fatty acids (SCFAs) and reduce detrimental bacteria in the gut [31] . Importantly, gut metabolites such as SCFAs may be a key to understanding gut-bone crosstalk.…”
Section: Osteomicrobiologymentioning
confidence: 99%